2007
DOI: 10.1177/1545109707300684
|View full text |Cite
|
Sign up to set email alerts
|

Statins Blunt HAART-Induced CD4 T-Cell Gains but Have No Long-Term Effect on Virologic Response to HAART

Abstract: Exposure to statins was associated with decreased CD4 T-cell gains during HAART in a cohort of HIV-infected patients, despite adequate virologic response. Studies with longer follow-up and detailed metabolic and immunologic monitoring are needed to confirm these findings and assess their significance and mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…However, sustained and co-expression of inhibitory receptors are hallmarks of exhausted T cells, which are prominent in chronic viral infections and cancer [ 2 , 3 , 32 ]. The use of statins as preventive and prophylactic measures for cancer therapy have been proposed [ 51 54 ] In addition, statins and other lipid-lowering drugs are administered to HIV patients to avert coronary heart disease [ 55 , 56 ]. In these studies reduction in percentages of TIM-3 and PD-1 by T cells in response to atorvastatin treatment have been reported [ 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, sustained and co-expression of inhibitory receptors are hallmarks of exhausted T cells, which are prominent in chronic viral infections and cancer [ 2 , 3 , 32 ]. The use of statins as preventive and prophylactic measures for cancer therapy have been proposed [ 51 54 ] In addition, statins and other lipid-lowering drugs are administered to HIV patients to avert coronary heart disease [ 55 , 56 ]. In these studies reduction in percentages of TIM-3 and PD-1 by T cells in response to atorvastatin treatment have been reported [ 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, laboratory studies have suggested that statins may inhibit HIV viral replication [3133]. However, the effect of statin on HIV RNA level in humans has not been consistently demonstrated [30,34]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, in small retrospective cohort studies, the data suggested that the use of statins was associated with lower CD4+ T cell responses in patients on HAART [70, 71]. In contrast, however, randomized controlled trials have not observed any changes in CD4 counts with statin therapy [54•, 72].…”
Section: Implications Of Immunological Effects Of Statins In the Hiv-mentioning
confidence: 99%
“…In contrast, however, randomized controlled trials have not observed any changes in CD4 counts with statin therapy [54•, 72]. Similarly, a number of studies have shown in vitro HIV inhibition with statins [7377], but this has not played out in vivo [53, 71, 72]. …”
Section: Implications Of Immunological Effects Of Statins In the Hiv-mentioning
confidence: 99%